Intracorporeal circular-stapled gastroduodenostomy for billroth I reconstruction in total laparoscopic distal gastrectomy - Yang, Ying; Zhou, Linsen; Zhuang, Jing; Sun, Yizhou; Ding, Yuemei; Jiang, Haohai (Frontiers in Surgery, 2025)
ObjectivesWhile laparoscopic distal gastrectomy (LDG) has gained acceptance for early gastric cancer, challenges persist in intracorporeal circular-stapled gastroduodenostomy during totally laparoscopic distal gastrectomy (TLDG). This study introduces a novel technique using a laparoscopic purse-string suture clamp (Lap-PSC) and multifunctional sealing cap (MSC) to simplify Billroth I circular-stapled anastomosis.MethodsA single-center retrospective analysis was conducted on 47 gastric cancer patients undergoing TLDG with Lap-PSC and MSC between September 2022 and June 2024. Surgical procedures involved D2 lymph node dissection, a 5 cm upper abdominal incision for specimen extraction, and intracorporeal circular-stapled anastomosis using Lap-PSC for duodenal purse-string suturing and MSC for pneumoperitoneum maintenance. Postoperative outcomes, complications, and anastomotic integrity were evaluated.ResultsAll 47 patients underwent successful TLDG with negative resection margins. Mean operative time was 148.3 ± 41.4 min. One patient (2.1%) experienced postoperative gastroparesis, and one patient (2.1%) experienced postoperative pneumonia. No anastomotic leaks, strictures, or perioperative deaths occurred. Median follow-up was 21.4 months (range: 13–34), with no recurrence or anastomosis-related complications.ConclusionTLDG with Circular-Stapled Gastroduodenostomy for Billroth I anastomosis demonstrates technical feasibility and safety, combining the precision of open surgery with laparoscopic minimally invasive benefits. The technique simplifies intracorporeal circular-stapled anastomosis, avoids excessive tension, and may reduce ischemic risks associated with linear stapler methods.